Technical requirements and devices available for long-term hemodialysis in children-mind the gap! - Ranchin, Bruno; Schmitt, Claus P.; Warady, Bradley A.; Hataya, Hiroshi; Jones, Joanne; Lalji, Rowena; Licht, Christoph; Mosca, Melodie; Stronach, Lynsey; Vidal, Enrico; Vande Walle, Johan; Shroff, Rukshana (Pediatric nephrology, 2024)
Children requiring long-term kidney replacement therapy are a "rare disease" cohort. While the basic technical requirements for hemodialysis (HD) are similar in children and adults, key aspects of the child's cardiovascular anatomy and hemodynamic specifications must be considered. In this article, we describe the technical requirements for long-term HD therapy for children and the devices that are currently available around the world. We highlight the characteristics and major technical shortcomings of permanent central venous catheters, dialyzers, dialysis machines, and software available to clinicians who care for children. We show that currently available HD machines are not equipped with appropriately small circuits and sensitive control mechanisms to perform safe and effective HD in the youngest patients. Manufacturers limit their liability, and health regulatory agencies permit the use of devices, only in children according to the manufacturers' pre-specified weight limitations. Although registries show that 6-23% of children starting long-term HD weigh less than 15 kg, currently, there is only one long-term HD device that is cleared for use in children weighing 10 to 15 kg and none is available and labelled for use in children weighing less than 10 kg anywhere in the world. Thus, many children are being treated "off-label" and are subject to interventions delivered by medical devices that lack pediatric safety and efficacy data. Moreover, recent improvements in dialysis technology offered to adult patients are denied to most children. We, in turn, advocate for concerted action by pediatric nephrologists, industry, and health regulatory agencies to increase the development of dedicated HD machines and equipment for children.
Veröffentlicht am 23 December 2023
Gesehen am 20.11.2024